Quizizz Application in Writing Class: A Comparative Study in A Senior High School - Sri Lestari; Imam Sudarmaji; Dini Khoerunnisa (Soegijapranata Catholic University, 2025)
This study examines the effectiveness of the Quizizz application in improving writing skills among tenth-grade students at State Senior High School in Tangerang. Utilizing a quasi-experimental design, the research involved 43 students in an experimental group using Quizizz and 43 students in a control group receiving traditional instruction. Data were collected through pretests and posttests to measure writing skill improvements, and a questionnaire to assess student perceptions of the application. The Wilcoxon Signed Rank Test revealed a significant increase in writing scores in the experimental group, with an average posttest score rising from [specific pretest score] to [specific posttest score]. These results suggest that Quizizz effectively enhances writing skills. The findings have implications for integrating digital tools in writing instruction and provide a foundation for future research on technology-enhanced learning methods